Communications, Cyber Resilience, and the Future of the U.S. Electric Power System: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Electric power is a critical infrastructure that is vital to the U.S. economy and national security. Today, the nation’s electric power infrastructure is threatened by malicious attacks, accidents, and failures, as well as disruptive natural events. As the electric grid evolves and becomes increasingly interdependent with other critical infrastructures, the nation is challenged to defend against these threats and to advance grid capabilities with reliable defenses. On November 1, 2019, the National Academies of Sciences, Engineering, and Medicine convened a workshop to gather diverse perspectives on current and future threats to the electric power system, activities that the subsector is pursuing to defend itself, and how this work may evolve over the coming decades. This publications summarizes the presentations and discussions from the workshop.
Keywords: Energy and Energy Conservation; Conflict and Security Issues

Strategies to Enhance Air Force Communication with Internal and External Audiences: A Workshop Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Air Force (USAF) helps defend the United States and its interests by organizing, training, and equipping forces for operations in and through three distinct domains -- air, space, and cyberspace. The Air Force concisely expresses its vision as "Global Vigilance, Global Reach, and Global Power for America." Operations within each of these domains are dynamic, take place over large distances, occur over different operational timelines, and cannot be routinely seen or recorded, making it difficult for Airmen, national decision makers, and the American People to visualize and comprehend the full scope of Air Force operations. As a result, the Air Force faces increasing difficulty in succinctly and effectively communicating the complexity, dynamic range, and strategic importance of its mission to Airmen and to the American people. To address this concern, the Chief of Staff of the USAF requested that the National Academies of Sciences, Engineering, and Medicine convene a workshop to explore options on how the Air Force can effectively communicate the strategic importance of the Service, its mission, and the role it plays in the defense of the United States. Participants worked to address the issues that a diverse workforce encompassing a myriad of backgrounds, education, and increasingly diverse current mission sets drives the requirement for a new communication strategy. The demographics of today's Air Force creates both a unique opportunity and a distinct challenge to Air Force leadership as it struggles to communicate its vision and strategy effectively across several micro-cultures within the organization and to the general public. This report summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Perspectives on Research with H5N1 Avian Influenza: Scientific Inquiry, Communication, Controversy: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2013)
When, in late 2011, it became public knowledge that two research groups had submitted for publication manuscripts that reported on their work on mammalian transmissibility of a lethal H5N1 avian influenza strain, the information caused an international debate about the appropriateness and communication of the researchers' work, the risks associated with the work, partial or complete censorship of scientific publications, and dual-use research of concern in general. Recognizing that the H5N1 research is only the most recent scientific activity subject to widespread attention due to safety and security concerns, on May 1, 2012, the National Research Council's Committee on Science, Technology and Law, in conjunction with the Board on Life Sciences and the Institute of Medicine's Forum on Microbial Threats, convened a one-day public workshop for the purposes of 1) discussing the H5N1 controversy; 2) considering responses by the National Institute of Allergy and Infectious Diseases (NIAID), which had funded this research, the World Health Organization, the U.S. National Science Advisory Board for Biosecurity (NSABB), scientific publishers, and members of the international research community; and 3) providing a forum wherein the concerns and interests of the broader community of stakeholders, including policy makers, biosafety and biosecurity experts, non-governmental organizations, international organizations, and the general public might be articulated. Perspectives on Research with H5N1 Avian Influenza: Scientific Enquiry, Communication, Controversy summarizes the proceedings of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The effective use of data science - the science and technology of extracting value from data - improves, enhances, and strengthens acquisition decision-making and outcomes. Using data science to support decision making is not new to the defense acquisition community; its use by the acquisition workforce has enabled acquisition and thus defense successes for decades. Still, more consistent and expanded application of data science will continue improving acquisition outcomes, and doing so requires coordinated efforts across the defense acquisition system and its related communities and stakeholders. Central to that effort is the development, growth, and sustainment of data science capabilities across the acquisition workforce. At the request of the Under Secretary of Defense for Acquisition and Sustainment, Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science assesses how data science can improve acquisition processes and develops a framework for training and educating the defense acquisition workforce to better exploit the application of data science. This report identifies opportunities where data science can improve acquisition processes, the relevant data science skills and capabilities necessary for the acquisition workforce, and relevant models of data science training and education.
Keywords: Conflict and Security Issues; Computers and Information Technology; Math, Chemistry, and Physics

Improving the Intelligence Community's Leveraging of the Full Science and Technology Ecosystem - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The agencies within the U.S. Intelligence Community (IC) depend on advanced technology to achieve their goals. While AI, cloud computing, advanced sensors, and big data analytics will fundamentally change both the global threat landscape and IC tradecraft, advances from biology, chemistry, materials, quantum science, network science, social/behavioral/economic sciences, and other fields also have that potential. Maintaining awareness of advances in science and technology is more essential than ever, to avoid surprise, to inflict surprise on adversaries, and to leverage those advances for the benefit of the nation and the IC. This report explores ways in which the IC might leverage the future research and development ecosystem.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Public Health Risks of Disasters: Communication, Infrastructure, and Preparedness: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2005)
The National Research Council's Disasters Roundtable and the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine were established as mechanisms for bringing various stakeholders together to discuss timely issues in a neutral setting. The goal was not to resolve these issues, but to create an environment conducive to scientific debate. The members of the respective Roundtables comprise representatives from academia, industry, nongovernmental agencies, and government, whose perspectives range widely and represent the diverse viewpoints of researchers, federal officials, and public interest. This report is the summary of a workshop was convened by the two Roundtables as a contribution to the debate on the health risks of disasters and the related need to build capacity to deal with them. The meeting was strengthened by integrating perspectives from these two fields, so that the agenda represented information from both communities and provided an opportunity to look at some of the most pressing research and preparedness needs for health risks of disasters.
Keywords: Earth Sciences; Health and Medicine; Conflict and Security Issues

Sensing and Supporting Communications Capabilities for Special Operations Forces: Abbreviated Version - National Research Council (The National Academies Press, 2009)
Among its key responsibilities, the U.S. Special Operations Command (SOCOM) plans and synchronizes operations against terrorist networks. At any given moment, SOF are likely to be engaged in some state of the planning or execution of special operations in many countries around the world, spanning a wide range of environments and mission. SOF therefore must be capable of operating in environments ranging from tropical jungle to arctic, maritime to desert, subterranean to mountainous, and rural to urban. Within this vast range additional factors may influence technical and operational requirements including weather, topography, bathymetry, geology, flora, fauna, and human population density. All of these factors must be weighed in terms of the challenges they pose to supporting communications and operational security. In short, SOF must maintain the capability to operate globally, in any environment, angainst any threats that can be countered by its unique capabilities. Sensing and Supporting Communications Capabilities for Special Operations Forces focuses primarily on the key core SOF task of special reconnaissance, to determine SOF-specific sensing and supporting communications needs and mapping them to existing and emerging technologies. The book discusses preliminary observations, issuees, and challenges, and identifies additional capabilities and technology areas that should be addressed.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

Network Science - National Research Council (The National Academies Press, 2005)
The military is currently attempting to develop itself into a force capable of networkcentric operations. While this effort has highlighted the military’s dependence on interacting networks, it has also shown that there is a huge gap between what we need to know about networks and our fundamental knowledge about network behavior. This gap makes the military vision of NCO problematic. To help address this problem, the Army asked the NRC to find out whether identifying and funding a new field of “network science” could help close this gap. This report presents an examination of networks andthe military, an analysis of the promise, content, and challenges of network science, and an assessment of approaches to creating value from network science.
Keywords: Computers and Information Technology; Conflict and Security Issues

Diplomacy for the 21st Century: Embedding a Culture of Science and Technology Throughout the Department of State - National Research Council (The National Academies Press, 2015)
Diplomacy for the 21st Century recommends steps that the Department of State should embrace to take full advantage of the leading science and technology (S&T) capabilities of the United States. These capabilities provide the department with many opportunities to promote a variety of the interests of the United States and its allies in a rapidly changing world wherein S&T are important drivers of economic development at home and abroad and help ensure international security. This report assesses and makes recommendations concerning the changing environment for the conduct of diplomacy in the years ahead, with a focus on the role of S&T in the development and implementation of U.S. policies and programs. According to this report, prompt steps by the department's leadership are essential to ensure adequate comprehension of the importance of S&T-related developments throughout the world and to incorporate this understanding within the nation's foreign policy for the 21st century. This report also urges the adoption by the department of a broader whole-of-society approach in carrying out its responsibilities at home and abroad - extending beyond traditional interagency coordination and the narrow band of current external partners to include foundations, universities, research centers, and other groups who are extending their international reach.
Keywords: Conflict and Security Issues

Determining Core Capabilities in Chemical and Biological Defense Science and Technology - National Research Council (The National Academies Press, 2012)
The goal of the U.S. Department of Defense's (DoD's) Chemical and Biological Defense Program (CBDP) is to provide support and world-class capabilities enabling he U.S. Armed Forces to fight and win decisively in chemical, biological, radiological, and nuclear (CBRN) environments. To accomplish this objective, the CBDP must maintain robust science and technology capabilities to support the research, development, testing, and evaluation required for the creation and validation of the products the program supplies. The threat from chemical and biological attack evolves due to the changing nature of conflict and rapid advances in science and technology (S&T), so the core S&T capabilities that must be maintained by the CBDP must also continue to evolve. In order to address the challenges facing the DoD, the Deputy Assistant Secretary of Defense (DASD) for Chemical and Biological Defense (CBD) asked the National Research Council (NRC) to conduct a study to identify the core capabilities in S&T that must be supported by the program. The NRC Committee on Determining Core Capabilities in Chemical and Biological Defense Research and Development examined the capabilities necessary for the chemical and biological defense S&T program in the context of the threat and of the program's stated mission and priorities. Determining Core Capabilities in Chemical and Biological Defense Science and Technology contains the committee's findings and recommendations. It is intended to assist the DASD CBD in determining the best strategy for acquiring, developing, and/or maintaining the needed capabilities.
Keywords: Conflict and Security Issues

Managing for High-Quality Science and Engineering at the NNSA National Security Laboratories - National Research Council (The National Academies Press, 2013)
The three National Security Laboratories--Los Alamos National Laboratory (LANL), Sandia National Laboratories (SNL), and Lawrence Livermore National Laboratory (LLNL)--are managed by private-sector entities under contract to the National Nuclear Security Administration (NNSA). The FY2010 Defense Authorization Act mandated that NNSA task the National Research Council (NRC) to study the quality and management of Science and Engineering (S&E) at these Laboratories. This study (addressing a total of 5 tasks) is being conducted in two phases. This report covers the first phase, which addresses the relationship between the quality of the science and engineering at the Laboratory and the contract for managing and operating the Laboratory (task 4), and also addresses the management of work conducted by the Laboratory for entities other than the Department of Energy (task 5). The study's second phase will evaluate the actual quality of S&E in key subject areas. Managing for High-Quality Science and Engineering at the NNSA National Security Laboratories presents assessments of the evolution of the mission of the NNSA Labs and the management and performance of research in support of the missions, and the relationship between the Laboratory Directed Research and Development (LDRD) program and the ability of the Labs to fulfill their mission. The report examines the framework for managing science and engineering research at the Labs and provides an analysis of the relationships among the several players in the management of the Labs--the NNSA, the site offices, the contractors, and the Lab managers--and the effect of that relationship on the Laboratories' ability to carry out science and engineering research.
Keywords: Conflict and Security Issues

The Science of Responding to a Nuclear Reactor Accident: Summary of a Symposium - National Research Council (The National Academies Press, 2014)
The Science of Responding to a Nuclear Reactor Accident summarizes the presentations and discussions of the May 2014 Gilbert W. Beebe Symposium titled "The Science and Response to a Nuclear Reactor Accident". The symposium, dedicated in honor of the distinguished National Cancer Institute radiation epidemiologist who died in 2003, was co-hosted by the Nuclear and Radiation Studies Board of the National Academy of Sciences and the National Cancer Institute. The symposium topic was prompted by the March 2011 accident at the Fukushima Daiichi nuclear power plant that was initiated by the 9.0-magnitude earthquake and tsunami off the northeast coast of Japan. This was the fourth major nuclear accident that has occurred since the beginning of the nuclear age some 60 years ago. The 1957 Windscale accident in the United Kingdom caused by a fire in the reactor, the 1979 Three Mile Island accident in the United States caused by mechanical and human errors, and the 1986 Chernobyl accident in the former Soviet Union caused by a series of human errors during the conduct of a reactor experiment are the other three major accidents. The rarity of nuclear accidents and the limited amount of existing experiences that have been assembled over the decades heightens the importance of learning from the past. This year's symposium promoted discussions among federal, state, academic, research institute, and news media representatives on current scientific knowledge and response plans for nuclear reactor accidents. The Beebe symposium explored how experiences from past nuclear plant accidents can be used to mitigate the consequences of future accidents, if they occur. The Science of Responding to a Nuclear Reactor Accident addresses off-site emergency response and long-term management of the accident consequences; estimating radiation exposures of affected populations; health effects and population monitoring; other radiological consequences; and communication among plant officials, government officials, and the public and the role of the media.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

Advancing Regulatory Science for Medical Countermeasure Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Whether or not the United States has safe and effective medical countermeasures--such as vaccines, drugs, and diagnostic tools--available for use during a disaster can mean the difference between life and death for many Americans. The Food and Drug Administration (FDA) and the scientific community at large could benefit from improved scientific tools and analytic techniques to undertake the complex scientific evaluation and decision making needed to make essential medical countermeasures available. At the request of FDA, the Institute of Medicine (IOM) held a workshop to examine methods to improve the development, evaluation, approval, and regulation of medical countermeasures. During public health emergencies such as influenza or chemical, biological, radiological/nuclear (CBRN) attacks, safe and effective vaccines, treatments, and other medical countermeasures are essential to protecting national security and the well being of the public. Advancing Regulatory Science for Medical Countermeasure Development examines current medical countermeasures, and investigates the future of research and development in this area. Convened on March 29-30, 2011, this workshop identified regulatory science tools and methods that are available or under development, as well as major gaps in currently available regulatory science tools. Advancing Regulatory Science for Medical Countermeasure Development is a valuable resource for federal agencies including the Food and Drug Administration (FDA), the Department of Health and Human Services (HHS), the Department of Defense (DoD), as well as health professionals, and public and private health organizations.
Keywords: Health and Medicine; Conflict and Security Issues

India-United States Cooperation on Science and Technology for Countering Terrorism: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2014)
India and the United States are the world's two largest democracies with distinguished scientific traditions and experts in a wide range of scientific-technical fields. Given these strengths and the ability to learn from one another, the U.S. National Academy of Sciences together with the National Institute for Advanced Studies in Bangalore, India, held a joint Indian-U.S. workshop to identify and examine potential areas for substantive scientific and technical cooperation that can support counterterrorism efforts through the Homeland Security Dialogue and through direct cooperation. India-United States Cooperation on Science and Technology for Countering Terrorism is the summary of that workshop. This report examines topics such as biological threats; protection of nuclear facilities; security (physical and cyber) for chemicals, chemical facilities and other critical infrastructure; and monitoring, surveillance, and emergency response. The report also identifies and examines promising areas for further Indian-U.S. cooperation.
Keywords: Conflict and Security Issues

Diplomacy for the 21st Century: Embedding a Culture of Science and Technology Throughout the Department of State: Summary - National Research Council (The National Academies Press, 2015)
Diplomacy for the 21st Century recommends steps that the department should embrace in order to take full advantage of the leading science and technology (S&T) capabilities of the United States. These capabilities provide the department with many opportunities to promote a variety of the interests of the United States and its allies in a rapidly changing world wherein S&T are important drivers of economic development at home and abroad and help ensure international security. This summary version highlights the main ideas and key messages of the full report.
Keywords: Conflict and Security Issues

An Assessment of Non-Lethal Weapons Science and Technology - National Research Council (The National Academies Press, 2003)
Non-lethal weapons (NLWs) are designed to minimize fatalities and other undesired collateral damage when used. Events of the last few years including the attack on the USS Cole have raised ideas about the role NLWs can play in enhancing support to naval forces. In particular to what extent and in what areas should Department of the Navy (DoN) -sponsored science and technology (S&T) provide a research base for developing NLW capabilities? To assist with this question and to evaluate the current NLWs program, the Joint Non-Lethal Weapons Directorate (JNLWD) and the Office of Naval Research (ONR) requested the National Research Council perform an assessment of NLWs science and technology. The report presents the results of that assessment. It discusses promising NLW S&T areas, development accomplishments and concerns about NLW, and series of recommendations about future NLW development and application.
Keywords: Conflict and Security Issues

Opportunities in Protection Materials Science and Technology for Future Army Applications - National Research Council (The National Academies Press, 2011)
Armor plays a significant role in the protection of warriors. During the course of history, the introduction of new materials and improvements in the materials already used to construct armor has led to better protection and a reduction in the weight of the armor. But even with such advances in materials, the weight of the armor required to manage threats of ever-increasing destructive capability presents a huge challenge. Opportunities in Protection Materials Science and Technology for Future Army Applications explores the current theoretical and experimental understanding of the key issues surrounding protection materials, identifies the major challenges and technical gaps for developing the future generation of lightweight protection materials, and recommends a path forward for their development. It examines multiscale shockwave energy transfer mechanisms and experimental approaches for their characterization over short timescales, as well as multiscale modeling techniques to predict mechanisms for dissipating energy. The report also considers exemplary threats and design philosophy for the three key applications of armor systems: (1) personnel protection, including body armor and helmets, (2) vehicle armor, and (3) transparent armor. Opportunities in Protection Materials Science and Technology for Future Army Applications recommends that the Department of Defense (DoD) establish a defense initiative for protection materials by design (PMD), with associated funding lines for basic and applied research. The PMD initiative should include a combination of computational, experimental, and materials testing, characterization, and processing research conducted by government, industry, and academia.
Keywords: Engineering and Technology; Conflict and Security Issues

Foundational Cybersecurity Research: Improving Science, Engineering, and Institutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Attaining meaningful cybersecurity presents a broad societal challenge. Its complexity and the range of systems and sectors in which it is needed mean that successful approaches are necessarily multifaceted. Moreover, cybersecurity is a dynamic process involving human attackers who continue to adapt. Despite considerable investments of resources and intellect, cybersecurity continues to poses serious challenges to national security, business performance, and public well-being. Modern developments in computation, storage and connectivity to the Internet have brought into even sharper focus the need for a better understanding of the overall security of the systems we depend on. Foundational Cybersecurity Research focuses on foundational research strategies for organizing people, technologies, and governance. These strategies seek to ensure the sustained support needed to create an agile, effective research community, with collaborative links across disciplines and between research and practice. This report is aimed primarily at the cybersecurity research community, but takes a broad view that efforts to improve foundational cybersecurity research will need to include many disciplines working together to achieve common goals.
Keywords: Computers and Information Technology; Conflict and Security Issues

The Quality of Science and Engineering at the NNSA National Security Laboratories - National Research Council (The National Academies Press, 2013)
The three National Nuclear Security Administration (NNSA) national security laboratories—Los Alamos National Laboratory (LANL), Lawrence Livermore National Laboratory (LLNL), and Sandia National Laboratories (SNL)—are a major component of the U.S. government's laboratory complex and of the national science and technology base. These laboratories are large, diverse, highly respected institutions with broad programs in basic sciences, applied sciences, technology development, and engineering; and they are home to world-class staff and facilities. Under a recent interagency agreement between the Department of Energy (DOE), Department of Defense, Department of Homeland Security, and the intelligence community, they are evolving to serve the needs of the broad national security community. Despite this broadening of substance and support, these laboratories remain the unique locus of science and engineering (S&E) for the U.S. nuclear weapons program, including, most significantly, the science-based stockpile stewardship program and the S&E basis for analyzing and understanding nuclear weapon developments of other nations and non-state actors. The National Research Council (NRC) was asked by Congress to assess the quality of S&E and the management of S&E at these three laboratories. The Quality of Science and Engineering at the NNSA National Security Laboratories is the second of two reports produced as part of this study. This report assesses the quality of S&E in terms of the capability of the laboratories to perform the necessary tasks to execute the laboratories' missions, both at present and in the future. The report identifies the following as four basic pillars of stockpile stewardship and non-proliferation analysis: (1) the weapons design; (2) systems engineering and understanding of the effects of aging on system performance; (3) weapons science base; and (4) modeling and simulation, which provides a capability to integrate theory, experimental data, and system design. The Quality of Science and Engineering at the NNSA National Security Laboratories offers a snapshot of the present with an eye to the future. This report discusses the current state of S&E and makes recommendations to maintain robust programs.
Keywords: Engineering and Technology; Math, Chemistry, and Physics; Conflict and Security Issues

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.
Keywords: Math, Chemistry, and Physics; Policy for Science and Technology; Conflict and Security Issues